A Analisis Kreativitas Anak Berkebutuhan Khusus Selama Masa Pandemi Covid-19 di Primagama Homeschooling - Cucu Retno Yuningsih (Jurnal Edukasi Sebelas April, 2020)
This study aims to determine the factors, the major influence of the Covid-19 pandemic on art learning for elementary school students with special needs at Primagama Homeschooling. This research can help the author to know the role of parents in helping children learn at home. The role of parents is considered very important in this case, because as long as students carry out learning activities at home, parents must replace teachers in their learning. The method used in this study is a qualitative descriptive method with data collection techniques through observation, interviews, documentation, and assisted by some literature as a means of gathering information. This research is considered a systematic activity, the aim is to carefully examine the answers that have been obtained. The instrument of this research is the researcher himself, and the triangulation method using effective observation criteria for interview guide data and documentation. Data analysis techniques include data analysis, presentation, and interpretation that describe the data qualitatively. The results of this study indicate that: 1) The level of creativity of students increases during work activities at home by utilizing used goods at home, 2) Parents have their own strategies in increasing the creativity of their children during art learning activities at home, 3 ) The delivery of fine arts subjects by the teacher at Primagama Homeschooling through online media is not monotonous and tries to use the TikTok application and canvas media as a means for students to express themselves.